Hak Kepemilikan Sisa Jahitan Ditinjau Dari KHES - Yusriani, Yusriani (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2022)
Sewing is the process of putting together pieces of fabric that have been cut based on a pattern. The sewing technique used must be in accordance with the design and materials, so that the sewing results are good and of good quality. The steps taken in the sewing process are: Prepare the sewing tools needed, such as sewing machines, hand needles, pins, pendedels, and irons. This research is a field research that directly takes data from the research location by using data sources, namely primary data and secondary data. The data collection used in this study is in the form of in-depth interviews (in-dept interviews) directly to tailors and customers. The time to conduct this research is about 2 months and the location of this research is in Hutagodang Muda Village, Siabu District, Mandailing Natal Regency. The subjects of this research are Tailors and their Customers. The results showed that the implementation of the ownership rights for the remaining stitches in Hutagodang Muda Village, Siabu District, Mandailing Natal Regency contained a lack of understanding of the law regarding the remaining stitches between the tailor and the customer, because the tailor did not return the remaining stitches to the customer measuring 1 meter, and this tailor processed the stitches. back the remaining stitches into a stitch, such as shirts, footwear, and hijab brooches, and she took advantage of the remaining stitches. In the Review of the Compilation of Sharia Economic Law on Ownership Rights of Remaining Stitches in Hutagodang Muda Village, Siabu District, Mandailing Natal Regency, where the ownership rights for the remaining stitches, if the customer gives or allows the remaining stitches to be owned by the tailor, the tailor has the right to rework the remaining stitches. that. However, if the customer does not give the remaining stitches to the tailor, then the tailor has no right to reprocess the remaining stitches.